Crystal structure and functional characterization of a cold-active acetyl xylan esterase (PbAcE) from psychrophilic soil microbe Paenibacillus sp. - Sun-Ha Park; Wanki Yoo; Chang Woo Lee; Chang Sook Jeong; Seung Chul Shin; Han-Woo Kim; Hyun Park; Kyeong Kyu Kim; T Doohun Kim; Jun Hyuck Lee (PLoS ONE, 2018)
Cold-active acetyl xylan esterases allow for reduced bioreactor heating costs in bioenergy production. Here, we isolated and characterized a cold-active acetyl xylan esterase (PbAcE) from the psychrophilic soil microbe Paenibacillus sp. R4. The enzyme hydrolyzes glucose penta-acetate and xylan acetate, reversibly producing acetyl xylan from xylan, and it shows higher activity at 4°C than at 25°C. We solved the crystal structure of PbAcE at 2.1-Å resolution to investigate its active site and the reason for its low-temperature activity. Structural analysis showed that PbAcE forms a hexamer with a central substrate binding tunnel, and the inter-subunit interactions are relatively weak compared with those of its mesophilic and thermophilic homologs. PbAcE also has a shorter loop and different residue composition in the β4-α3 and β5-α4 regions near the substrate binding site. Flexible subunit movements and different active site loop conformations may enable the strong low-temperature activity and broad substrate specificity of PbAcE. In addition, PbAcE was found to have strong activity against antibiotic compound substrates, such as cefotaxime and 7-amino cephalosporanic acid (7-ACA). In conclusion, the PbAcE structure and our biochemical results provide the first example of a cold-active acetyl xylan esterase and a starting template for structure-based protein engineering.